A visualized probe method for localization of surface oxygen vacancy on TiO2: Au in situ reduction. Issue 41 (6th October 2015) - Zheng, Zuyang; Fang, Zhibin; Ye, Xinxin; Yao, Xiaobin; Fu, Xianzhi; Lin, Sen; Liu, Ping
Abstract : Surface oxygen vacancy has been investigated extensively. Studies involving location of oxygen vacancy is still rare. Here, a visualized method is developed to fill in the gap. Applications of it can be extended to other defects and noble metals. Abstract : Surface oxygen vacancy has been investigated extensively due to its great influence on photocatalysis in recent years. Among these investigations, the location of surface defects is found to be a key factor during the photocatalytic procedure. Especially when a crystal facet is involved, the synergistic action between these two factors may greatly increase the photocatalytic efficiency. Location of defects would greatly help in understanding the mechanism of this coupling action. Without an available technique, however, it is very difficult to gain the position information directly. In this paper, we provide a low-cost and visualized method to solve this problem via in situ reduction of Au. TiO2 with surface oxygen vacancy on a specific area is synthesized via a photochemical reaction. Then the Au ion was reduced at the place where oxygen vacancy exists on the TiO2 surface. Hence, the localization of surface vacancy will be determined by examining the location of Au particles. Moreover, application of this method can be extended to other surface defects such as oxygen vacancy on oxide semiconductors, Ti 3+ in TiO2, Zn vacancy on ZnO, etc. This technique is helpful for understanding how surface defects affect the properties of semiconductors.